(untitled) - Busby, Thomas L. (Hoboken, NJ, 2007)
Praise for The Markets Never Sleep "An excellent primer for futures and the global financial market, a clear voice of their importance for all traders. Tom also gives an easy-to-understand professional approach to discipline, money management, and the 'numbers' to watch that indicate market direction.
Keywords: Capital market,Stock exchanges,Invesments,Thị trường vốn,Trao đổi chứng khoán,Đầu tư